Quercetin modulates the gut microbiota as well as the metabolome in a rat model of osteoarthritis. Issue 1 (1st January 2021) - Lan, Haifeng; Hong, Wei; Qian, Dongyang; Peng, Fang; Li, Haiqing; Liang, Chunxiao; Du, Min; Gu, Jinlan; Mai, Junxuan; Bai, Bo; Peng, Gongyong
ABSTRACT: Although the mechanism of osteoarthritis (OA) has been widely studied and the use of quercetin for OA therapy is well documented, the relevant characteristics of the microbiome and metabolism remain unclear. This study reports changes in the gut microbiota and metabolism during quercetin therapy for OA in a rat model and provides an integrative analysis of the biomechanism. In this study, the rats were categorized into 3 different groups: the OA model, quercetin treatment, and control groups. The OA rats was conducted using a monoiodoacetate (MIA) injection protocol. The rats in the quercetin group received daily intragastric administration of quercetin from day 1 to day 28. Stool samples were collected, and DNA was extracted. We used an integrated approach that combined the sequencing of whole 16S rRNA, short-chain fatty acid (SCFA) measurements and metabolomics analysis by mass spectrometry (MS) to characterize the functional impact of quercetin on the gut microbiota and metabolism in a rat model of OA. The use of quercetin partially abrogated intestinal flora disorder and reversed fecal metabolite abnormalities. Compared with the control rats, the OA rats showed differences at both the class level ( Clostridia, Bacteroidia, and Bacilli ) and the genus level ( Lactobacillus and unidentified Ruminococcaceae ). Acetic acid, propionic acid and 24 metabolites were significantly altered among the three groups. However, the changes were significantly abrogated in quercetin-treated OA rats. Consequently, this study provided important evidence regarding perturbations of the gut microbiome and the function of these changes in a potential new mechanism of quercetin treatment. Graphical ABSTRACT: uf0001